A Study on Behaviour of V and Trapezoidal Type of Folded Plate Roofs for Fixed and Hinged Boundary Conditions - LaxmiYerdoor, Roopa; R Suresh, Y. (International Journal of Engineering and Technology, 2026)
Folded plate roofs are very useful form of roof structures for spanning large column free areas, which composed of a number of flat thin plates connected to each other. In this paper, linear static analysis is performed to study the behaviour of two types of single span prismatic folded plate roof. Different parameters considered for the study are height, bay width, thickness and varying boundary conditions. The results are obtained in the form of variation of displacement and percentage reduction in displacement for different thickness which are useful for selecting economic sections and predicting stiffness.
Keywords: Folded Plate roof; Linear static analysis; Prismatic; Displacements; Bay width; Finite element analysis; Stiffness.